2013
DOI: 10.3748/wjg.v19.i45.8398
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio predicts the prognosis of patients with hepatocellular carcinoma after liver transplantation

Abstract: A preoperative elevated NLR significantly increased the risk for tumor recurrence in HCC patients after LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
1
37
0
1
Order By: Relevance
“…In particular, the neutrophil-lymphocyte ratio (NLR) has been evaluated as a predictor of prognosis in various types of solid tumor, including gastric, colorectal, pancreatic, breast and lung cancers (16)(17)(18)(19)). An elevated NLR has already been shown to be associated with poor prognosis in patients with HCC treated by liver transplantation, surgical resection, or TACE (20)(21)(22). The present study evaluated the association between peripheral blood neutrophil count and the prognosis of HCC treated with sorafenib, and revealed peripheral neutrophil count as a prognostic factor in such cases.…”
Section: Introductionmentioning
confidence: 72%
“…In particular, the neutrophil-lymphocyte ratio (NLR) has been evaluated as a predictor of prognosis in various types of solid tumor, including gastric, colorectal, pancreatic, breast and lung cancers (16)(17)(18)(19)). An elevated NLR has already been shown to be associated with poor prognosis in patients with HCC treated by liver transplantation, surgical resection, or TACE (20)(21)(22). The present study evaluated the association between peripheral blood neutrophil count and the prognosis of HCC treated with sorafenib, and revealed peripheral neutrophil count as a prognostic factor in such cases.…”
Section: Introductionmentioning
confidence: 72%
“…Recent studies have shown that NLR values are highly associated with the prognosis of diseases related to inflammation [8,9]. High NLR values have also been shown to be referring to the poor prognosis in different types of cancers [10,11,12,13]. In a study evaluating cases of acute appendicitis, NLR is found to elicit acute appendicitis with a high sensitivity and specificity when comparing it to WBC and CRP values [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some potential markers of recurrence are tumor size, tumor number, differentiation, vascular invasion, and the serum concentration of alpha-fetoprotein (AFP) [6]. Various biological and dynamic variables have been proposed in both Western and Eastern scenarios, such as AFP dynamics, radiological response to locoregional treatments, and several inflammatory markers, the most promising of which is the neutrophil-to-lymphocyte ratio [7]. …”
Section: Introductionmentioning
confidence: 99%